The association between HLA‐DQB1 polymorphism and antituberculosis drug‐induced liver injury: a Case–Control Study. (24th September 2014) - Chen, R.; Zhang, Y.; Tang, S.; Lv, X.; Wu, S.; Sun, F.; Xia, Y.; Zhan, S. Y.
Summary What is known and objective Research on genetic factors associated with antitubercular drug‐induced liver injuries (ATLI) has been reported. However, most of the research has focused on genetic polymorphisms of genes encoding metabolic enzymes, including NAT2, GST and CYP450. It is probable that the immune system also contributes to the onset of drug adverse effects. A few small studies have explored the possible association of HLA genes with drug‐induced liver injuries (DILI), but more supportive evidence from larger studies or prospective cohort designs is needed. We aim to explore the possible association of HLA‐DQB1 gene polymorphisms with ATLI in a case–control study. Methods A case–control study design was used. ATLI was recorded in a prospectively followed‐up cohort of patients receiving antituberculosis treatment. Identified cases were matched with control tuberculosis patients within the same cohort but with no adverse effects in 1 : 1 ratio. We used the sequence‐based typing method to determine the HLA‐DQB1 genotypes. Odds ratios (OR) and 95% confidence intervals (CI) were calculated using conditional logistic regression. Results and discussion Eighty‐nine cases were included in this case–control study. HLA‐DQB1 typing was successful for 177 subjects. No association between frequency of HLA‐DQB1 genotypes and ATLI was statistically significant in univariate analyses. Multivariate analysis using the conditional logistic regression model revealed that the individuals with two DQB1*05 alleles were at higher risk of ATLI than control subjects. The OR was 5·28 adjusted for use of liver protective drugs and weight (10/88 VS 2/88, 95% CI: 1·134‐24·615, P = 0·034). Analysis according to the liver injury type showed that both mixed liver injury patients and cholestatic/mixed liver injury patients had higher proportions of DQB1*05 : 02 alleles (P values were 0·028 and 0·005, respectively). What is new and conclusion This study suggests that ATLI was more likely in subjects of HLA‐DQB1*05/*05 genotype. Further studies are needed to verify this association.